A new editorial project, a new Journal for health sciences - Ubillús-Trujillo, Milward (2019)
The central core and raison d'être of the University of this century, in a universal sense, is the generation of knowledge through scientific research; which is generally focused on science and technology with the participation of all its researchers, generating creative solutions to the multiple problems of the community in which it develops and develops.